Moral Education of Children Streets In PPAP Seroja Surakarta - Badrus Zaman (Edukasia Islamika, 2019)
The research objectives to be achieved are: To find out the concept of moral education given by the PPAP Seroja institution to street children in Surakarta, what factors influence the difficulty of applying moral education in PPAP Seroja Surakarta, and the level of moral development of street children after being provided with moral education at the PPAP Seroja Surakarta institution. This type of research is a descriptive qualitative study conducted at PPAP Seroja Surakarta in 2019, data collected through the method of observation, documentation, and interviews. The analysis was conducted using interactive analysis with three components namely data reduction, data presentation, and drawing conclusions. The conclusions of the study are as follows: Moral education in street children at PPAP Seroja Surakarta, which involves fostering good moral attitudes and behavior or good character and is expected to help in the moral development of street children in forming character, good character of citizenship, who has good morals. Factors that influence the difficulty of implementing moral education in PPAP Seroja Surakarta are street children who do not have the awareness to attend moral education, lack of competency, less supportive infrastructure, and family environment that tends to be passive and far from moral values. The level of moral development of street children after being provided with moral education at PPAP Seroja Surakarta is at the conventional level, namely at level III (orientation to the group of "sweet children" or "good children") and level IV (law and order orientation).